2007
DOI: 10.1615/critrevimmunol.v27.i6.30
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ Memory T Lymphocytes from Bone Marrow— Immune Function and Therapeutic Potential

Abstract: Immunity to previously encountered diseases is provided in large part by memory T lymphocytes, which may be subdivided based on phenotypic and functional differences, as well as the specific cellular compartments in which these cells reside. The bone marrow (BM) is a unique microenvironment that supports robust proliferation and recall responses of both "central" and "effector" memory T cells, particularly within the CD8+ T cell subset. The recent identification within human BM of a population of CD8+ effector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…26 This observation suggests that in Ph ϩ ALL patients in complete remission the normal differentiation, recirculation, and activation potential of BM T lymphocytes do not appear to be negatively affected, even during high-dose IM. In patient 1, who showed sustained complete molecular remission, the almostexclusive presence of the EMRA subset among BM CD8 ϩ T cells may possibly be consistent with the notion that EMRA T cells appear late during the immune response and proliferate in the absence of the antigen.…”
Section: Discussionmentioning
confidence: 87%
“…26 This observation suggests that in Ph ϩ ALL patients in complete remission the normal differentiation, recirculation, and activation potential of BM T lymphocytes do not appear to be negatively affected, even during high-dose IM. In patient 1, who showed sustained complete molecular remission, the almostexclusive presence of the EMRA subset among BM CD8 ϩ T cells may possibly be consistent with the notion that EMRA T cells appear late during the immune response and proliferate in the absence of the antigen.…”
Section: Discussionmentioning
confidence: 87%
“…In this context, antigen specific CD8 + T cells which express interleukin-7 receptor α (CD127 + ) show enhanced proliferation in response to homeostatic signals and most likely develop into long-lasting memory cells. IL-7 stimulation is crucial for memory T cell survival and proliferation, and a high IL-7Rα/CD127 expression warrants these cells with the ability to persist for long period in the absence of antigen stimulation [21,36]. CD127 may therefore, be considered as a useful marker to identify effector lymphocytes precursors destined to differentiate into memory cells [22].…”
Section: Resultsmentioning
confidence: 99%
“…It is essential that the RSV specific memory T cells persist after primary infection to keep enduring immunological protection. The mechanisms behind the development of long-lasting memory cells are incompletely understood but, recently, it was shown that IL-7Rα + effector cells are able to survive antigen deprivation and develop into long living memory CD8 + T cells [22,36]. To this aim, we characterized the CD8 + CD127 + long-lasting memory cells specific to RSV by pentamer in healthy subjects of three different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some current cancer vaccine strategies may fail because they amplify, rather than correct or reset, the corrupted CD81 memory population. 26 However, it is becoming apparent that highly activated effector cells may become terminally differentiated, display impaired proliferation and survival in vivo, and mediate short-term antitumor effects.…”
Section: Cd81 Cellsmentioning
confidence: 99%